(untitled) (ResearchJet Journal of Analysis and Inventions, 2023)
Ustrushana has been one of the developed regions of Central Asia since ancient times. That is why its geographical location, population, political processes, and material and cultural life details are widely reflected in ancient authors, early medieval Chinese and Sugdian written sources, and historical-geographical works in Arabic and Persian languages.